Effect of insole material and wear condition on heel cushioning of running shoes - Ong, Jean Hui Min (2018)
This study investigated the effect of insole materials and wear condition on heel cushioning of running shoes. Three insole materials, namely, open-cell foam, close-cell foam and gel were selected for comparison. These insoles were compared amongst each other when new and after they had been worn for a fixed number of steps. The insoles were compared according to the peak force and displacement upon impact. Using the data from the impact trials, the energy dissipated relative to the energy absorbed by the shoe upon impact were calculated and compared amongst the insoles. A higher amount of energy dissipated leads to greater damping. Thus, a higher energy dissipated to energy absorbed ratio was desired. This energy ratio would be used to determine the cushioning properties of the insoles.